Pengaruh Model Inkuiri Terbimbing Terhadap Hasil Belajar Peserta Didik Kelas VII Pada Materi Interaksi Makhluk Hidup Dengan Lingkungannya - Lailu, Benedikta Rambu Peda; Djalo, Aloysius; Ndukang, Sardina (JBIOEDRA: Jurnal Pendidikan Biologi, 2024)
The low learning outcomes of students in science learning, particularly biology, are due to the perception that biology material is difficult and boring. One way to improve students' learning outcomes is by using the guided inquiry learning model. This study aims to determine the effect of the guided inquiry learning model on the learning outcomes of Grade VII students in the topic of interactions between living organisms and their environment at SMPK St. Agustinus Adisucipto Penfui Kupang.The sample for this research consisted of Grade VII C students as the experimental class, using the guided inquiry learning model, and Grade VII D students as the control class, using the direct instruction model. The type of research employed was quantitative with a quasi-experimental design. The research design used was the Nonequivalent Control Group Design. Data analysis techniques included descriptive analysis and inferential analysis. The results of the study showed that the average learning mastery of students in the experimental class had a pretest score of 53.23 and a posttest score of 81.61, with an N-Gain of 0.60, categorized as high. Meanwhile, the control class had an average pretest score of 45.5 and a posttest score of 72.5, with an N-Gain of 0.48, categorized as moderate. Based on the ANCOVA test results, the significance value was 0.001 < 0.05, which led to the rejection of the null hypothesis (Ho) and the acceptance of the alternative hypothesis (Ha). Thus, it can be concluded that the guided inquiry learning model significantly affects the learning outcomes of Grade VII students in the topic of interactions between living organisms and their environment at SMPK St. Agustinus Adisucipto Penfui Kupang.